ChemInform Abstract: Thionium‐Based One‐Pot Construction of Homo‐/Heterodimeric Pyrroloindoline from Tryptamine. Issue 1 (January 2015) - Tayu, Masanori; Higuchi, Kazuhiro; Ishizaki, Takako; Kawasaki, Tomomi
Abstract A one‐pot dimerization of two tryptamine derivatives is developed to yield homo‐ as well as heterodimeric mixtures of racemic (IV) and meso (V) products.